Two new dammarane-type triterpene saponins from Korean red ginseng and their anti-inflammatory effects. Issue 23 (1st December 2017) - Vinh, Le Ba; Lee, Yunjeong; Han, Yoo Kyong; Kang, Jong Seong; Park, Jung Up; Kim, Young Ran; Yang, Seo Young; Kim, Young Ho
Graphical abstract: Abstract: Panax ginseng has been the subject of extensive research on potential medicinal materials. The goal of this study was search the chemical constituents and biological activities of processed Panax ginseng, Korean red ginseng. Our efforts led to the isolation eleven compounds (1 –11 ) including two new compounds1 and2 from Korean red ginseng using various chromatographic techniques. Chemical structures of isolated compounds were demonstrated by spectroscopic methods (1D-, 2D-NMR, and HR-ESI-MS). The anti-inflammatory effects of the compounds were investigated by inhibiting IL-6 and TNF-α secretion in LPS-activated RAW264.7 cells. Additionally, the effects of the compounds on the expression of COX-2 and iNOS were examined by Western blotting. Compound1 significantly reduced the level of proinflammatory cytokines IL-6 and TNF-α secretion in LPS-activated RAW264.7 cells and the expression of COX-2 and iNOS inflammatory enzymes in the cells. These results suggested that compound1, a new ginsenoside might useful in treatment of inflammation.